Changing norms around women in agribusiness among young Tanzanians – Phase 3 - International Livestock Research Institute (Shujaaz Inc, 2023)
Building on the success of the first two phases of our collaboration with ILRI, Shujaaz Inc will launch an expanded campaign from February to December 2023 to shift norms related to young women working in the poultry and dairy businesses, in line with ILRI’s new SAPLING programme. The proposed additional support from ILRI will enable Shujaaz Inc to reach 1.8 million young people with meaningful messages about agri-preneurship ensuring the digital campaign effectively engages not just young women but also a range of influencers and gatekeepers capable of both reinforcing and shifting the gender norms surrounding young women in agribusiness. A key aspect of Phase 3 will be regular knowledge-sharing with ILRI and key stakeholders to review and process findings from Shujaaz’s continuous data analysis and insight generation. Throughout the campaign we will also develop a relationship with Kuza Biashara and other ILRI partners to amplify their work and direct young Shujaaz fans to their programmes.